Luonnonkiviverhotut massiivitiilirakennukset Suomessa - Lahdensivu, Jukka (Tekniikan Waiheita, 2013)
Natural stone-faced brick-walled buildings in Finland Towards the end of the 19th century and early 20th century approximately 150-200 natural stone-faced solid brick-walled buildings were constructed in Finland. The intensive building period lasted only 20 years, which means the building technology as well as building materials remained same all the period. The buildings built during that period were considered very Finnish, although both the architectural style and building technology were imported from Sweden and Central Europe. The use of natural stone as façade material for buildings started relatively late in Finland compared to the rest of Europe. It peaked in the so-called national romantic period. Natural stone facades were also built later, but the style was more rational. Buildings constructed by the same technique for example in Sweden are somewhat older, most date back to 1860–1890. The external wall assembly consists of a bearing brick wall and natural stone facing, generally selfsupporting, on the exterior surface. The gap between the brick wall and the natural stone facing is filled with mortar which prevents ventilation. The interior face of the external wall is usually plastered level, and the surface is treated with different painting methods. The total thickness of the brick wall has varied in the 450–1500 mm range, while thickness of natural stone varied typically between 10–300 mm. The thinnest brick walls are found in low buildings and church gables. The thickest ones appear in walls of churches and other massive buildings, especially in the lower sections. The natural stone facing has been attached to the brick wall by different methods. Most often steel tie rods and socalled bond stones and combinations of them have been used. The natural stone facade may also have been laid of stones so thick that their bonding to the brick wall could be done mainly by mortar. Such buildings are generally quite low.